1996
DOI: 10.1021/ie950510f
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Measurement of Oxidation in Supercritical Water. 1. Conversion of Methanol to Formaldehyde

Abstract: The oxidation rate of methanol and the subsequent production and destruction of the primary intermediate, formaldehyde, were investigated using Raman spectroscopy as an in situ analytical method. Experiments were conducted in supercritical water over temperatures ranging from 440 to 500 °C at 24.1 MPa and at a nominal feed concentration of 0.05 mol/L (1.5 wt %). Effluent samples were also examined using gas chromatography. In these experiments, feed concentrations ranging from 0.011 to 1.2 wt % and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 33 publications
4
97
0
Order By: Relevance
“…An experimentally determined expression for the homogeneous dissociation of H,O, is derived and incorporated into a methanol oxidation model. The new prediction is compared with the experimental data of Rice et al (1996), showing a distinct improvement compared to the original prediction.…”
Section: Introductionmentioning
confidence: 99%
“…An experimentally determined expression for the homogeneous dissociation of H,O, is derived and incorporated into a methanol oxidation model. The new prediction is compared with the experimental data of Rice et al (1996), showing a distinct improvement compared to the original prediction.…”
Section: Introductionmentioning
confidence: 99%
“…9) There are many papers on in situ Raman spectroscopy to observe chemical species in supercritical water. [10][11][12][13][14][15][16][17][18][19][20] It is guessed that in these papers Raman spectroscopy is completed within several hours, although Gorbaty and Bondarenko reported a cell design which withstood high temperature and high pressure above critical point of water for one week. 16) For in situ Raman spectroscopy for corrosion monitoring, long-term observation is indispensable, typically for several hundred hours and in some cases several thousand hours.…”
Section: Introductionmentioning
confidence: 99%
“…Direct observations of small-scale, transparent reactors (e.g., diamond anvil cells or quartz capillary tubes) allow reactions to be seen, photographed, and quickly halted if necessary (Azadi & Farnood, 2011;Fang et al, 2008;Hashaikeh et al, 2007;Maharrey & Miller, 2001;Peterson et al, 2008a;Sasaki et al, 2000;Vogel et al, 2005). Larger scale systems have been directly observed via optical, laser Raman spectroscopy through sapphire reactor viewing ports in order to capture finite details of the reaction progress, fluid mechanics, reactant destruction completeness, and oxidation efficiencies (Chuntanapum & Matsumura, 2010;García-Verdugo et al, 2004;Hunter et al, 1996;Koda et al, 2001;Rice et al, 1996). Indirect, nuclear radiography accomplishes the same result as optical Raman spectroscopy, but does not require viewing-port reactor modifications (Peterson et al, 2008a(Peterson et al, , 2008b(Peterson et al, , 2010.…”
Section: Reactor Kinetics and Design Considerationsmentioning
confidence: 99%
“…Newer reaction-observation techniques show promise for developing an understanding of the missing, critical kinetics needed for comprehensive modeling of SCWG reactions (Vogel et al, 2005). Reaction observation techniques (particularly Raman spectroscopy), nonetheless, are not widely used, are limited to methodological studies, and have no comprehensive kinetics models based on them Rice et al, 1996). Existing observation studies have, however, partially confirmed the assumptions that endothermic, acidcatalyzed hydrolysis reactions quickly dissolve sludge educts before they can dehydrate, resulting in complete solubilization and liquefaction early in the process (Brunner, 2009b;Koda et al, 2001;Peterson et al, 2008a).…”
Section: Reactor Kinetics and Design Considerationsmentioning
confidence: 99%